Brazilian companies initial public offering during the years 2004 and 2005: reasons and perceptions (Revista de Administração, 2007)
The current favorable scenery of the international economy, and the Brazilian´s recent economic growth, is taking national companies to identify opportunities of expanding its operations and reorganizing its capital structure, what has made the number of opened capital companies in the stock market raise recently. This work aims to identify the main reasons that influenced some companies, during 2004 and 2005, to initiate the process of capital opening in the stock market, and which were their perceptions after the process. A multiple case study was applied in Brazilian companies that hads their capital opened in the stock exchange between january 2004 and september 2005. The results showed that the companies opted for opening their capital aiming to adopt a valorization and growth strategy, as well as financing its projects of expansion. After the opening, the companies perceived organizational changes in the corporative governance, in the auditors´ roles, in the directors commitment and in accountability practices. All the companies demonstrated satisfaction with the results of the process.